Improving interpersonal communication: positive thinking training for santri Pondok Pesantren Tahfidz Qur'an An-Nur Gemolong Sragen - Sidiq Rahmadi; Sapardi Sapardi; Danang Bimo Aji; Agus Ekoyono; Taufik Kasturi (Universitas Muhammadiyah Magelang, 2023)
This Community service aims to help students maintain their interpersonal connections to other people and their environment by increasing understanding and motivation. In order to establish comfort in studying, be skilled at handling challenges, and maintain mental health, it is intended that the students would be able to forge strong relationships with peers, teachers, and the neighborhood surrounding the boarding school. The community service implementation strategy that consists of three stages: introduction, induction, and evaluation. The outcome of this program is that students understand the difference between thinking positively and negatively. Students are encouraged to grow in self-assurance, develop empathy for friends, adhere to the boarding school's norms with more order, be more forthright when they encounter difficulties, and be able to appreciate others more. Thus, the impact is the improving understanding of the students regarding the importance of positive thinking in interpersonal communication, so that students can establish harmonious relationships with their environment.